BO‘LAJAK O‘QITUVCHILARNI RAQAMLASHTIRISH SHAROITLARIDA ELEKTRON TA’LIM RESURSLARINI YARATISHGA O‘QITISh METODIKASINI TAKOMILLASHTIRISH - Nurmaxanov, K.E. (SCIENCE and SOCIETY, 2023)
The article discusses the current problem of preparing future teachers for the professional implementation of digitalization of education. Curriculum and subject changes are necessary to integrate student competencies into learning experiences, digital technologies, and pedagogical goals. The personal place and preparation of the future teacher should be concerned with the methods of teaching school discipline based mainly on digitalization. The author proposes a new “digital” teacher qualification and the concept of personality and individuality.